PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN KINERJA KEUANGAN PERUSAHAAN - Darma Yanti (Jurnal Ilmiah Ekonomi Global Masa Kini)
This study titled disclosure of corporate social responsibility (CSR) and corporate financial performance. This study aimed to examine the effect of disclosure CorporateSocial Responsibility (CSR) on the performance keuangan.Selain the researchers used the ratio ROS (return on sales), EPS (earnings per share), and stock prices to evaluate the performance of the controls used keuangan.Variabel is leverage , firm size (size), and institutional ownership. Leverage provides information on funding liabilities remain firm and its ability to meet the obligations of this funding. This study describes the influence of corporate social responsibility (CSR), leverage, company size, and institutional ownership tehadap financial performance is proxied by the ratio of ROS (return on sales), EPS (earnings per share), and stock prices. The population in this study are all mining and manufacturing companies listed in Indonesia Stock Exchange (BEI) in the period 2011-2013 amounted to 105 companies. The method used in the selection of the sample in this research is purposive sampling, with specific criteria, that the financial statements of companies sampled ended December 31, 2011, 2012, and 2013.Based on data analysis, we concluded that the disclosure of corporate social responsibility (CSR) has no effect on the financial performance return on sales (ROS) but positive effect on earnings performance pr share (EPS) and stock prices (HG_SHM). It is therefore not accepted hypothesis 1a, 1b and 1c while the hypothesis is accepted.Keywords: Influence of corporate social responsibility (CSR), leverage, company size, and institutional ownership of financial performance